A comparison of one year outcomes between standardized locomotor training and usual care after motor incomplete spinal cord injury: Community participation, quality of life and re-hospitalization. (2nd January 2023) - Tefertiller, Candace; Rozwod, Meghan; Wojciehowski, Sandra; Sevigny, Mitch; Charlifue, Susan; Ketchum, Jessica M.; Berliner, Jeffrey; Taylor, Heather B.; Behrman, Andrea L.; Harkema, Susan; Forrest, Gail; Schmidt Read, Mary; et al.
Abstract : Context/Objective: Spinal cord injury (SCI) often results in a significant loss of mobility and independence coinciding with reports of decreased quality of life (QOL), community participation, and medical complications often requiring re-hospitalization. Locomotor training (LT), the repetition of stepping-like patterning has shown beneficial effects for improving walking ability after motor incomplete SCI, but the potential impact of LT on psychosocial outcomes has not been well-established. The purpose of this study was to evaluate one year QOL, community participation and re-hospitalization outcomes between individuals who participated in a standardized LT program and those who received usual care (UC). Design/Setting/Participants: A retrospective (nested case/control) analysis was completed using SCI Model Systems (SCIMS) data comparing one year post-injury outcomes between individuals with traumatic motor incomplete SCI who participated in standardized LT to those who received UC. Outcome Measures: Outcomes compared include the following: Satisfaction with Life Scale (SWLS™), Craig Handicap Assessment and Reporting Technique-Short Form (CHART-SF™), and whether or not an individual was re-hospitalized during the first year of injury. Results: Statistically significant improvements for the LT group were found in the following outcomes: SWLS (P = 0.019); and CHART subscales [mobility (P = <0.001)]; occupation (P = 0.028); with small to medium effects sizes. Conclusion: Individuals who completed a standardized LT intervention reported greater improvements in satisfaction with life, community participation, and fewer re-hospitalizations at one year post-injury in comparison to those who received UC. Future randomized controlled trials are needed to verify these findings.